Effects of amines and polyamines on turbidimetric and lysoplate assays for lysozyme. - Jenzano, J W (1988)
The lysoplate and turbidimetric assays have often been used to measure lysozyme in biological fluids, such as blood and saliva. When the same purified lysozyme standard is used in both assays, results obtained with the lysoplate assay are much higher than those obtained for the same sample in the turbidimetric assay. It is likely, therefore, that other components in the biological fluid sample influence the expression of lysozyme activity in one or both assays to produce such divergent results. Certain amines or polyamines are found in various biological fluids and have the potential to influence the reactions in these two assay systems. It was the purpose of this study to incorporate selected amines and polyamines into purified lysozyme preparations and saliva or into the assay preparations to compare their effects on observed lysozyme activity between the two assay systems. Results showed that when the amine or polyamine was included in the purified sample, lysozyme activity was considerably greater than that of controls in the lysoplate assay, whereas a negligible effect was observed in the turbidimetric assay. If the amine or polyamine was incorporated into the assay preparation, results were more dramatic, with large increases in activity in the lysoplate assay and concomitant inhibition in the turbidimetric assay. Similar effects were observed in the assay of lysozyme in saliva, suggesting a potential mechanism by which the two assay systems produce markedly different results for the same sample.